Prediagnostic circulating concentrations of plasma insulin‐like growth factor‐I and risk of lymphoma in the European Prospective Investigation into Cancer and Nutrition. Issue 5 (27th December 2016) - Perez‐Cornago, Aurora; Appleby, Paul N.; Tipper, Sarah; Key, Timothy J.; Allen, Naomi E.; Nieters, Alexandra; Vermeulen, Roel; Roulland, Sandrine; Casabonne, Delphine; Kaaks, Rudolf; Fortner, Renee T.; Boeing, Heiner; et al.
Abstract : Insulin‐like growth factor (IGF)‐I has cancer promoting activities. However, the hypothesis that circulating IGF‐I concentration is related to risk of lymphoma overall or its subtypes has not been examined prospectively. IGF‐I concentration was measured in pre‐diagnostic plasma samples from a nested case–control study of 1, 072 cases of lymphoid malignancies and 1, 072 individually matched controls from the European Prospective Investigation into Cancer and Nutrition. Odds ratios (ORs) and confidence intervals (CIs) for lymphoma were calculated using conditional logistic regression. IGF‐I concentration was not associated with overall lymphoma risk (multivariable‐adjusted OR for highest versus lowest third = 0.77 [95% CI = 0.57–1.03], p trend  = 0.06). There was no statistical evidence of heterogeneity in this association with IGF‐I by sex, age at blood collection, time between blood collection and diagnosis, age at diagnosis, or body mass index ( p heterogeneity for all  ≥ 0.05). There were no associations between IGF‐I concentration and risk for specific BCL subtypes, T‐cell lymphoma or Hodgkin lymphoma, although number of cases were small. In this European population, IGF‐I concentration was not associated with risk of overall lymphoma. This study provides the first prospective evidence on circulating IGF‐I concentrations and risk of lymphoma. Further prospective data are required to examine associations of IGF‐I concentrations with lymphoma subtypes. Abstract : What's new? Insulin‐like growth factor I does not appear to influence lymphoma risk, according to new results. IGF‐I can promote some cancers, but there hasn't been a prospective epidemiological study examining the link between IGF‐I concentration and lymphoma risk. To uncover a link, these authors arranged a NESTED case–control study with participants from the European Prospective Investigation into Cancer and Nutrition (EPIC). They tested for IGF‐I in pre‐diagnosis samples and found no association between the factor and overall lymphoma risk, nor with any subtype, although the number of cases was small for each subtype, and further studies are necessary.